Exploring Teachers' and Pupils' Perceptions towards the Use of Gamification in Algerian Primary Schools The Case of Fourth Year Pupils at Chouibia Mohammed Taher Primary School in Souk Ahras - Bechichi Naoufel (My University, 2024)
ABSTRACT Exploring teachers' and pupils' perceptions about the use of gamification in primary schools in Algeria is a pivotal step towards understanding its potential impact on educational practices. The aim of this study is to delve into these perceptions, specifically focusing on 4th-year pupils at Chouibia Mohammed Taher Primary School in Souk Ahras. Gamification, the application of game-design elements in educational contexts, has shown promise in enhancing student engagement and learning. This research employs two questionnaires one for teachers and one for pupils—to gather detailed insights into their views on the effectiveness, benefits, and challenges of gamification in the classroom. The findings aim to provide valuable information for educators and policymakers to inform the implementation of gamification strategies, ultimately contributing to improved educational practices and outcomes in Algerian primary schools. By examining real-world classroom dynamics, this study bridges the gap between theoretical potential and practical application. It also offers a foundation for future research on innovative educational techniques in similar contexts. ---------------------- ‫ملخص‬ ‫استكشاف‬‫تصورات‬ ‫المعلمين‬ ‫والتالميذ‬ ‫حول‬ ‫استخدام‬ ‫التلعيب‬ ‫في‬ ‫المدارس‬ ‫االبتدائية‬ ‫في‬ ‫الجزائر‬ ‫يُعَد‬ ‫خطوة‬ ‫حاسمة‬ ‫نحو‬ ‫فهم‬ ‫تأثيره‬‫المحتمل‬ ‫على‬ ‫الممارسات‬ ‫التعليمية‪.‬‬ ‫تهدف‬ ‫هذه‬ ‫الدراسة‬ ‫إلى‬ ‫التعمق‬ ‫في‬ ‫هذه‬ ‫التصورات‪،‬‬ ‫مع‬ ‫التركيز‬ ‫بشكل‬ ‫خاص‬ ‫على‬ ‫تالميذ‬‫ال‬ ‫سنة‬ ‫الرابعة‬ ‫في‬ ‫مدرسة‬ ‫شعيبية‬ ‫محمد‬ ‫طاهر‬ ‫االبتدائية‬ ‫في‬ ‫سوق‬ ‫أهراس‪.‬‬ ‫لقد‬ ‫أظهرت‬ ‫التلعيب‪،‬‬ ‫وهي‬ ‫تطبيق‬ ‫عناصر‬ ‫تصميم‬‫األلعاب‬ ‫في‬ ‫السياقات‬ ‫التعليمية‪،‬‬ ‫وعدا‬ ‫ً‬ ‫في‬ ‫تعزيز‬ ‫تفاعل‬ ‫الطالب‬ ‫وتعلمهم‪.‬‬ ‫تعتمد‬ ‫هذه‬ ‫البحث‬ ‫على‬ ‫استبيانين‬ ‫‪-‬‬ ‫واحد‬ ‫للمعلمين‬‫وآخر‬ ‫للتالميذ‬ ‫‪-‬‬ ‫لجمع‬ ‫رؤى‬ ‫تفصيلية‬ ‫حول‬ ‫آ‬ ‫رائهم‬ ‫بخصوص‬ ‫فعالية‬ ‫وفوائد‬ ‫وتحديات‬ ‫التلعيب‬ ‫في‬ ‫الفصول‬ ‫الدراسية‪.‬‬ ‫تهدف‬‫النتائج‬ ‫إلى‬ ‫تقديم‬ ‫معلومات‬ ‫قيمة‬ ‫للمربين‬ ‫وصانعي‬ ‫السياسات‬ ‫إلرشاد‬ ‫تنفيذ‬ ‫استراتيجيات‬ ‫التلعيب‪،‬‬ ‫مما‬ ‫يساهم‬ ‫في‬ ‫نهاية‬ ‫المطاف‬‫في‬ ‫تحسين‬ ‫الممارسات‬ ‫والنتائج‬ ‫التعليمية‬ ‫في‬ ‫المدارس‬ ‫االبتدائية‬ ‫الجزائرية‪.‬‬ ‫من‬ ‫خالل‬ ‫فحص‬ ‫الديناميكيات‬ ‫الواقعية‬ ‫للفصول‬‫الدراسية‪،‬‬ ‫تسد‬ ‫هذه‬ ‫الدراسة‬ ‫الفجوة‬ ‫بين‬ ‫اإلمكانات‬ ‫النظرية‬ ‫والتطبيق‬ ‫العملي‪.‬‬ ‫كما‬ ‫أنها‬ ‫تقدم‬ ‫أساسا‬ ‫ً‬ ‫لألبحاث‬ ‫المستقبلية‬ ‫‪.‬حول‬‫التقنيات‬ ‫التعليمية‬ ‫المبتكرة‬ ‫في‬ ‫سياقات‬ ‫مشابهة‬ ------------------------ Résumé Explorer les perceptions des enseignants et des élèves sur l'utilisation de la gamification dans les écoles primaires en Algérie est une étape cruciale pour comprendre son impact potentiel sur les pratiques éducatives. Cette étude vise à approfondir ces perceptions, en se concentrant spécifiquement sur les élèves de 4ème année de l'école primaire Chouibia Mohammed Taher à Souk Ahras. La gamification, qui est l'application d'éléments de conception de jeux dans des contextes éducatifs, a montré des promesses pour améliorer l'engagement et l'apprentissage des élèves. Cette recherche utilise deux questionnaires - un pour les enseignants et un pour les élèves - pour recueillir des informations détaillées sur leurs opinions concernant l'efficacité, les avantages et les défis de la gamification en classe. Les résultats visent à fournir des informations précieuses aux éducateurs et aux décideurs pour informer la mise en œuvre des stratégies de gamification, contribuant ainsi à l'amélioration des pratiques et des résultats éducatifs dans les écoles primaires algériennes. En examinant les dynamiques réelles des salles de classe, cette étude comble le fossé entre le potentiel théorique et l'application pratique. Elle offre également une base pour de futures recherches sur les techniques éducatives innovantes dans des contextes similaires.